Airborne particulate matter (PM2.5) triggers autophagy in human corneal epithelial cell line. (August 2017) - Fu, Qiuli; Lyu, Danni; Zhang, Lifang; Qin, Zhenwei; Tang, Qiaomei; Yin, Houfa; Lou, Xiaoming; Chen, Zhijian; Yao, Ke
Abstract: Purpose: To investigate particulate matter (PM2.5)-induced damage to human corneal epithelial cells (HCECs) and to determine the underlying mechanisms. Methods: HCECs were exposed to PM2.5 at a series of concentrations for various periods. Cell viability was measured by using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Cell proliferation was evaluated via 5-ethynyl-2'-deoxyuridine (EdU) analysis, while autophagy was determined by immunofluorescence and Western blot. Results: PM2.5-induced cell damage of HCECs occurred in a time- and dose-dependent manner. Decreased cell viability and proliferation as well as increased apoptosis were observed in HCECs after PM2.5 exposure for 24 h. Autophagy in HCECs was slightly inhibited in the early stage (before 4 h) of exposure but significantly activated in the late stage (after 24 h), as evidenced by a decrease in the former and increase in the latter of the expression of the autophagy-associated markers LC3B, ATG5, and BECN1. Interestingly, rapamycin, an autophagy activator, attenuated early-stage but aggravated late-stage PM2.5-induced cell damage, suggesting that the role of autophagy in HCECs may change over time during PM2.5 exposure. In addition, in the early stage, the expression of LC3B and ATG5 increased in cells co-treated with rapamycin and PM2.5 compared to rapamycin-only or PM2.5-only treated cells, suggesting that autophagy may benefit cell viability after PM2.5 exposure. Conclusions: The results indicate the potential role of autophagy in the treatment of PM2.5-induced ocular corneal diseases and provide direct evidence for the cytotoxicity, possibly involving an autophagic process, of PM2.5 in HCECs. Graphical abstract: Highlights: PM2.5 induce cytotoxicity in HCECs in a time- and dose-dependent manner. Autophagy plays an essential role in PM2.5-induced HCECs dysfunction. Activation of autophagy attenuates PM2.5-induced cytotoxicity in the early stage. Abstract : The present study provides the first evidence that PM2.5 exposure results in HCECs dysfunction, in which autophagy plays an essential role.